Sosialisasi Pemanfaatan Limbah Kulit Kopi Dalam Upaya Perbaikan Kualitas Tanah - Ansiska, Paisal; Asep; Helmi, Dewilna; Windari, Ela Hasri; Oktoyoki, Hefri (INCOME: Indonesian Journal of Community Service and Engagement, 2022)
The amount of coffee husk waste has the potential as a pollutant in the environment if it is not managed properly. Making compost made from coffee husk as organic fertilizer is an effort that can be done to reduce the impact caused by coffee husk waste and at the same time as an effort to improve soil quality. This socialization activity aims to provide awareness and understanding of the impact of coffee skin waste and at the same time how to utilize the waste. This activity was carried out in the Social Forestry Business group (KUPS) Register Lima in Tebat Pulau Village, Bermani ulu sub-district, Rejang Lebong Regency, Bengkulu Province. Methods of counseling and interactive discussions through the zoom meeting application. After this socialization activity was carried out, there was an increase in public awareness and understanding regarding the use of leather waste in improving soil quality.